A BRIEF LOOK AT COMPUTERS. (Personnel & Guidance Journal)
The article focuses on basic ideas about computers and data processing. Data processing is the use of computers to rapidly store, retrieve, and display information. The two essential components of data processing are: the computer equipment or hardware; and the systems of programs, or software which enable the computer to perform its job. A computer operates through five main functions: input, storage, control, processing, and output. A man solving a problem with a calculating machine uses these same five functions. The computer takes in data by sensing or reading information from one of many sources. Another form of input is data entered into the computer by a keyboard that looks much like a typewriter. When reduced to bare fundamentals, Computers are capable of only two arithmetic operations-adding one number to another and comparing two numbers to see if they are equal. But they can perform these simple operations so rapidly and in so complex an interacting network that they can solve enormous problems when those problems are properly stated by men.